Ecomorphological convergence in the walking leg dactyli of two clades of ascidian‐ and mollusc‐associated shrimps (Decapoda: Caridea: Palaemonidae) - Werner deGier; Pepijn Helleman; Jurriaan van denOever; Charles H. J. M. Fransen (Ecology and Evolution, 2023)
Abstract Symbiotic species, living within or on the surface of host organisms, may evolve a wide range of adaptations as a result of various selection pressures, host specificity of the symbiont and the nature of the symbiosis. In tropical marine coral reef ecosystems, palaemonid shrimps (Crustacea: Decapoda: Caridea) live in association with at least five different invertebrate phyla. Host switches between (distantly) related host groups, and the thereby associated selection pressures were found to play a major role in the diversification of these shrimp lineages, giving rise to various host‐specific adaptations. Two lineages of palaemonid shrimp, which have switched from an ectosymbiotic association towards endosymbiosis, are studied for their morphological diversification and possible convergence. Special attention is given to the between‐phyla host switches involving ascidian and bivalve hosts, which are characteristic for these lineages. Using landmark‐based (phylo)morphospace analyses and Scanning Electron Microscopy, the walking leg dactylus shape and the microstructures on these dactyli are studied. No specific bivalve‐ or ascidian‐associated morphotypes were found, but morphological convergence in dactylus morphology was found in various species within the two studied clades with similar host groups. In addition, multiple lineages of bivalve‐associated species appear to be morphologically diverging more than their ascidian‐associated relatives, with ‘intermediate’ morphotypes found near host‐switching events.